Wound drainage following groin dissection for malignant disease in adults - Thomson, DR; Sadideen, H; Furniss, D (Wiley, 2014)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the current level of evidence regarding whether placement of a drain is beneficial after groin dissection in terms of reducing haematoma, seroma, wound dehiscence and wound infection rates. If it is, the optimal type and duration of drainage following groin dissection will also be determined.